A 12‐gene signature to distinguish colon cancer patients with better clinical outcome following treatment with 5‐fluorouracil or FOLFIRI. (9th April 2015) - Paquet, Eric R.; Cui, Jing; Davidson, David; Pietrosemoli, Natalia; Hassan, Houssein Hajj; Tsofack, Serges P.; Maltais, Annie; Hallett, Michael T.; Delorenzi, Mauro; Batist, Gerald; Aloyz, Raquel; Lebel, Michel
Abstract Currently, there is no marker in use in the clinical management of colon cancer to predict which patients will respond efficiently to 5‐fluorouracil (5‐FU), a common component of all cytotoxic therapies. Our aim was to develop and validate a multigene signature associated with clinical outcome from 5‐FU therapy and to determine if it could be used to identify patients who might respond better to alternate treatments. Using a panel of 5‐FU resistant and sensitive colon cancer cell lines, we identified 103 differentially expressed genes providing us with a 5‐FU response signature. We refined this signature using a clinically relevant DNA microarray‐based dataset of 359 formalin‐fixed and paraffin‐embedded (FFPE) colon cancer samples. We then validated the final signature in an external independent DNA microarray‐based dataset of 316 stage III FFPE samples from the PETACC‐3 (Pan‐European Trails in Alimentary Tract Cancers) clinical trial. Finally, using a drug sensitivity database of 658 cell lines, we generated a list of drugs that could sensitize 5‐FU resistant patients using our signature. We confirmed using the PETACC‐3 dataset that the overall survival of subjects responding well to 5‐FU did not improve with the addition of irinotecan (FOLFIRI; two‐sided log‐rank test p = 0.795). Conversely, patients who responded poorly to 5‐FU based on our 12‐gene signature were associated with better survival on FOLFIRI therapy (one‐sided log‐rank test p = 0.039). This new multigene signature is readily applicable to FFPE samples and provides a new tool to help manage treatment in stage III colon cancer. It also provides the first evidence that a subgroup of colon cancer patients can respond better to FOLFIRI than 5‐FU treatment alone.